Pelatihan Pengembangan Sistem Monitoring Suhu, Kelembapan dan Kadar CO2 di Udara Berbasis Internet of Things: Training on Monitoring System Development of a Temperature, Humidity, and Air CO2 Level Based on the Internet of Things - Bakti, Andi Ikhtiar; As'ari, As'ari; Rahman, Asep (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The temperature, humidity, and CO2 level monitoring system based on the Internet of Things provides real-time data with a high level of accuracy, accessible through technological devices such as smartphones, tablets, and notebooks. A commonly used IoT platform for this purpose is Blynk. In vocational high schools, students have been taught theoretically but have not implemented it effectively. Therefore, a community service activity was conducted through training on developing a temperature, humidity, and CO2 level monitoring system based on the Internet of Things for 50 students at SMK Negeri 1 Tomohon. This training is purposeful to provide students with knowledge and skills in using the temperature, humidity, and CO2 level monitoring system based on the Internet of Things. The methods used in this activity included socialization, training, practical sessions, demonstrations, and evaluations. Based on the training results, 90% of the students were able to understand the material well. The students were able to create a temperature, humidity, and CO2 level monitoring system based on the Internet of Things with good results.